2020
DOI: 10.3390/plants9111605
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Comparative Genomics, Codon Usage Bias, and Phylogenetic Relationship of Species from Biebersteiniaceae and Nitrariaceae Based on Complete Chloroplast Genomes

Abstract: Biebersteiniaceae and Nitrariaceae, two small families, were classified in Sapindales recently. Taxonomic and phylogenetic relationships within Sapindales are still poorly resolved and controversial. In current study, we compared the chloroplast genomes of five species (Biebersteinia heterostemon, Peganum harmala, Nitraria roborowskii, Nitraria sibirica, and Nitraria tangutorum) from Biebersteiniaceae and Nitrariaceae. High similarity was detected in the gene order, content and orientation of the five chloropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 54 publications
10
11
0
Order By: Relevance
“…9), the result is consistent with previous studies [93,96]. In the LSC analysis, Sapindaceae was sister to the Burseraceae + Anacardiaceae + Nitrariaceae clade (BS = 49, PP = 0.99, Figure S1), In the SSC analysis, Sapindaceae was sister to the Rutaceae + Simaroubaceae + Meliaceae clade (BS = 52, PP = 1, Figure S2), which is similar to the previous work [95,97]. Overall, as the sister group of Sapindaceae, most results exhibited weak support in maximum likelihood analysis.…”
Section: Features Of Complete Chloroplast Genome and Comparative Analysessupporting
confidence: 92%
See 1 more Smart Citation
“…9), the result is consistent with previous studies [93,96]. In the LSC analysis, Sapindaceae was sister to the Burseraceae + Anacardiaceae + Nitrariaceae clade (BS = 49, PP = 0.99, Figure S1), In the SSC analysis, Sapindaceae was sister to the Rutaceae + Simaroubaceae + Meliaceae clade (BS = 52, PP = 1, Figure S2), which is similar to the previous work [95,97]. Overall, as the sister group of Sapindaceae, most results exhibited weak support in maximum likelihood analysis.…”
Section: Features Of Complete Chloroplast Genome and Comparative Analysessupporting
confidence: 92%
“…However, the present analyses could not demonstrate the paraphyly of the Aesculus because of lacking su cient samples. In this study, we found Eurycorymbus cavaleriei as sister to Dodonaea viscosa with strong support (PP = 1.00, BS = 100), which similar to previous studies[45,47, 48,74,95]. Buerki et al[17, 18] conducted molecular phylogenetic studies of Sapindaceae s. lat.…”
supporting
confidence: 89%
“…Analyzing codon usage is essential to evaluate the evolution of the chloroplast genome (Chi et al, 2020; Sun et al, 2021). RSCU values were computed for the C .…”
Section: Resultsmentioning
confidence: 99%
“…Analyzing codon usage is essential to evaluate the evolution of the chloroplast genome (Chi et al, 2020;Sun et al, 2021). RSCU values were computed for the C. glandulifera, C. velutina, and L. chinense chloroplast genomes based on the protein-coding sequences.…”
Section: Codon Usage Analysismentioning
confidence: 99%
“…Codon usage bias in evolution research has been reported on model organisms, including E. coli ( Krisko et al, 2014 ), Dengue virus ( Manokaran et al, 2019 ), S. cerevisiae , Drosophila melanogaster ( Kliman et al, 2003 ), and humans ( Sauna and Kimchi-Sarfaty, 2011 ), as well as studies assessing codon usage in plant evolution research ( Rensing et al, 2005 ; Liu et al, 2010 ; Sahoo et al, 2019 ; Chi et al, 2020 ). Plant species are broadly diverse in their gene expression, physiology, and stress response in varied environments.…”
Section: Introductionmentioning
confidence: 99%